Balance Sheet Effects and the Choice of Exchange Rate Regime in Developing Countries - Bleaney, Michael (2012)
We investigate the choice of regime amongst hard pegs, soft pegs, managed floats and independent floats for a panel of developing countries. There is evidence of a matched ordering of regimes and country characteristics. We find some evidence for the 'balance sheet' hypothesis that foreign liabilities in the banking system and foreign debt are associated with less exchange rate flexibility, particularly when a 'de facto' regime classification is used. Easily the best predictor of a country's current regime is its regime in the previous year.